How to Measure the Tax Burden on Labour at the Macro-Level? - Jan-Egbert Sturm; Bjørn Volkerink (Center for Economic Studies and ifo Institute (CESifo), 2003)
The purpose of this paper is threefold. First, we survey the way in which the tax burden on labour has been proxied for in recent multi-country macro-economic studies. Second, we critically evaluate these proxies. Finally, we examine to what extent the conclusions of some studies change if some alternative indicator for the tax burden on labour is employed. We conclude that the widely used tax ratios as developed by Mendoza et al. (1994) may not be very reliable. The choice of the indicator for the tax burden on labour is also shown to affect the conclusions of some well-known empirical models.
Keywords: H20; H29; 330; tax ratios; labour; average effective tax rates; unemployment